Determinants Influencing Beef Cattle Development Prospects in Kolaka Regency, Southeast Sulawesi, Indonesia - Astarika, Rina; Jabuddin, La Ode; Abdi, Abdi; Zulkarnain, Deki; Munadi, La Ode Muhammad (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2024)
The beef cattle farming business in Kolaka Regency still has bright prospects for its development. The purpose of this study was to analyze the prospects and determine the development of beef cattle in Kolaka Regency. This study was centered in Watubangga District because it is the base area for beef cattle development. The research variables include the social characteristics of farmers and production costs, involving 45 farmers as respondents. The data analysis method used in this research is the Revenue-Cost approach and the Cobb-Douglas production function using the natural logarithm model. The research results show that the beef cattle business in Kolaka Regency has prospects or is profitable for development with an R/C ratio of 3,12. Meanwhile, the variables of total production and investment costs determine the prospects for developing beef cattle farming in Kolaka Regency. Therefore, support from across sectors is needed to improve the beef cattle business in the future, especially in terms of accessibility of business funding sources.